A multiplex bacterial assay using an element-labeled strategy for 16S rRNA detection. Issue 21 (28th August 2020) - Zhang, Yuqing; Sun, Gongwei; Hu, Zhian; Xing, Zhi; Zhang, Sichun; Zhang, Xinrong
Abstract : A direct multiplex bacterial assay via enzyme treatment and combinatorial elemental tagging probes without strain purification. Abstract : A multiplex bacterial assay method that combines S1 nuclease pretreatment and ICP-MS-based elemental labels is presented in this work. Six intestinal related bacteria were identified at the species level and quantified simultaneously without isolation culturing. This method could be extended to assay a mixed bacterial community for point-of-care diagnosis.